Malformation and Isolation: Critique to Jewish Orthodoxy Found in Franz Kafka’s "The Metamorphosis" - Anindya Firda Khairunnisa (Lexicon, 2015)
The research discusses the Jewish images found in The Metamorphosis by Franz Kafka and its interpretation. It aims to prove that the utilization of Jewish images within the novella shows the author’s underlying critique towards Jewish Orthodoxy’ ways of thinking, particularly the way they regard the Holy Scripture. The data used in the research are taken from Franz Kafka’s The Metamorphosis, in the form of words containing plot structure, characters and characterizations (including dialogue and actions), metaphors, symbols, and allusions, which represents a certain Jewish value within Kafka’s The Metamorphosis. The data are then analysed with Freudian Psychoanalysis, supported by external data such as the background of the author and information about Orthodox Judaism. The result of the research concluded that, in The Metamorphosis, Franz Kafka demonstrates that in front of the unquestioned and oblivious masses of the divine law human is hopeless; just like Gregor who ends up dying an unjustified death.